THE IMPACT OF PHYSICAL ACTIVITY ON DEMENTIA IN ELDERLY AGE - Barbara Starosta; Bartosz Brzychcy; Zuzanna Gajda; Monika Pelczar; Karolina Brzychcy; Karolina Paks; Ewa Jench; Natalia Musialik; Maciej Magiera (International Journal of Innovative Technologies in Social Science, 2025)
Population aging represents one of the greatest public health challenges of the 21st century. As global life expectancy continues to rise, the number of individuals affected by dementia is steadily increasing. Dementia is currently the seventh leading cause of death worldwide and a major contributor to disability and dependence among older adults. It is a clinical syndrome characterized by the progressive decline of cognitive functions such as memory, thinking, comprehension, and planning. The gradual loss of these abilities profoundly affects individuals’ daily functioning and quality of life, ultimately leading to increasing dependence, reduced autonomy, and social isolation. This imposes a significant burden not only on patients and their families but also on healthcare and social support systems. In the absence of effective disease-modifying therapies, preventive strategies and the identification of modifiable risk factors have become a primary focus of research and public health policy. Physical inactivity is now widely recognized as one of these modifiable risk factors. Purpose: The aim of this paper is to present the current state of knowledge regarding the relationship between physical activity and the risk of developing dementia in older age. Other modifiable risk factors for this condition will also be highlighted. The paper will discuss both the biological mechanisms through which physical activity affects cognitive functions and the findings of epidemiological and interventional studies supporting its protective role. Recommendations for physical activity as a component of preventive strategies in aging populations will also be outlined. Materials and Methods: A comprehensive literature search was performed using the PubMed database, focusing on studies published between 2010 and 2025. Search terms included "dementia", "cognitive disorders", “elderly” and "physical activity". As part of our methodological analysis, we selected 27 publications that met the criteria of evidence-based medicine (EBM). The reviewed literature included studies based on meta-analyses as well as the most recent guidelines issued by leading international scientific societies. Relevant articles were selected and critically assessed to extract and evaluate key findings and conclusions. Conclusions: Recent evidence from systematic reviews and meta-analyses underscores the critical role of modifiable risk factors in accelerating brain aging and cognitive decline. As life expectancy increases, there is a growing need to prioritize public health education and promote physical activity to prevent dementia and maintain quality of life in aging populations.